Educating students about time perspective and its effect on subjective well-being. Issue 5 (28th May 2022) - Kuan, Tat-Yeung James; Zhang, Li-Fang
Abstract: Four hundred and twelve secondary school students in Hong Kong responded to the Zimbardo Time Perspective Inventory (ZTPI), the Positive and Negative Affect Schedule (PANAS), and the Temporal Satisfaction with Life Scale (TSWLS) to examine the relationship between time perspective and subjective well-being. Past-Positive, Present-Hedonistic, and Future time perspectives predicted higher levels of subjective well-being, whereas Past-Negative and Present-Fatalistic time perspectives predicted lower levels of subjective well-being. Of the 412 students, 149 volunteered to take part in an intervention to optimise their time perspectives. After coarsened exact matching was applied, the results showed that the intervention optimised students' time perspective profile with a significant increase in Present-Hedonistic time perspective and reduction in Past-Negative and Present-Fatalistic time perspectives. It also led to a significant increase in positive affect, past and future life satisfaction for the students in the experimental group compared with those in the control group.